Beliefs and perceptions that impair cleft care treatment in Madagascar: A qualitative study during humanitarian mission - Nirina Adrien Jean Vivier Mandrano; Yasuyoshi Tosa; Tomoaki Kuroki; Nobuhiro Sato; Shinya Yoshimoto (Wolters Kluwer Medknow Publications, 2017)
Context: During humanitarian cleft care mission in developing countries, a considerable noncompliance of the patient remains evident despite the provided medical support. According to the literature, social background and beliefs are some of the factors that hamper cleft management in these areas. Aims: In this study, we investigated on these impairments for a better approach to cleft care in Madagascar. Settings and Design: This is a qualitative study conducted in Clinic Ave Maria, Antsirabe, Madagascar, which interviewed parents and patients. Subjects and Methods: One adult patient and nineteen parents of a patient with cleft lip and palate (CLP) were interviewed for a qualitative study. An open-ended, closed-ended semistructured interview was conducted. Results: Analysis of the interview result and a literature discussion were performed. The most believed cause of cleft lip was supernatural forces, diet, and a curse, leading to a strong self-blame and shame inside the community. Thus, CLP is thought to be a supernatural disease, which cannot be totally healed by injection and surgery. A belief leads to a delay, denial of medical care, and/or ignorance and rejection of new explanations. Conclusions: Social background and beliefs of our Malagasy community have a considerable impact on how the patients perceive cleft deformity. These perceptions strongly influence the patient's compliance to medical care. Considering education as a part of the treatment plan during a humanitarian mission can modify the patient's attitude and improve their motivation to a better treatment outcome.